STRATEGIC DA’WAH IN ISLAMIC MARRIAGE EDUCATION: REFRAMING THE ROLE OF RELIGIOUS COUNSELORS IN CONTEMPORARY MUSLIM SOCIETY - Elce Purwandari; Neri Silvika; Depi Putri (J-MD Jurnal Manajemen Dakwah, 2026)
The transformation of contemporary Muslim society has significantly affected family resilience, marital stability, and religious awareness within family life. Increasing divorce rates, digital cultural influences, and limited premarital preparedness indicate the urgent need for more adaptive Islamic marriage education. This study aims to analyze the strategic role of da’wah in Islamic marriage education through institutional religious counseling perspectives and to examine how strategic communication and counseling contribute to strengthening family resilience in contemporary Muslim society. The study employs a qualitative approach using a library research design. Data were collected through document analysis of scholarly books, peer-reviewed journal articles, and institutional publications related to strategic da’wah, Islamic counseling, communication strategies, and marriage education. The collected data were analyzed using thematic analysis to identify conceptual patterns and theoretical relationships within the scholarly discourse. The findings reveal that strategic da’wah has transformed Islamic marriage education from a merely normative religious activity into a preventive and transformative educational framework aimed at strengthening emotional maturity, communication ethics, and social responsibility among Muslim communities. The study also demonstrates that participatory communication, adaptive counseling approaches, and institutional educational management significantly influence the effectiveness of Islamic marriage education. Furthermore, digital communication technology encourages religious institutions to reconstruct traditional counseling methods into more innovative and socially responsive educational strategies. Theoretically, this study contributes to the development of Manajemen Da’wah scholarship by integrating communication, counseling, and institutional educational perspectives into a unified conceptual framework for Islamic marriage education.